Analisis yuridis pengelompokan wilayah pada notaris berkaitan norma perhitungan penghasilan neto terkait pejabat umum - Amanda Puteri Rachmatullah; Tunggul Anshari; Diah Aju Wisnuwardhani (Jurnal Cakrawala Hukum, 2021)
The NPPN regulations in PER DIRJEN PAJAK Number 17 / PJ / 2015 state that the NPPN percentage is grouped by region. Where this grouping of regions causes a difference in the percentage between regional groups. In addition, regulations regarding regional grouping are also found in PERMENKUMHAM Number 27/2016 which divides regional categories for the position of notaries. For the purpose of this research, this type of normative legal research uses a statute approach where the legal materials in this study are analyzed using prescriptive analysis techniques. Based on the results of the author's research, it can be concluded that the NPPN grouping by region is one of the manifestations of the Equality principle where this principle provides the same treatment to people who are in the same condition. The sentence is in the same condition can be interpreted as being in the same regional characteristics which are based on considerations using several variables. Broadly speaking, there is a correlation between the regional grouping of the two regulations, which lies in the basic factor for determining regional grouping, that is regional economic growth. The regional grouping that is regulated in the two rules has also fulfilled the value of justice as proposed by Aristotle's theory of justice. Regional grouping which is regulated by the government has clear and firm reasons so that this grouping is not a discriminatory act but is a form of distributive justice.How to cite item: Rachmatullah, A., Anshari, T., Wisnuwardhani, D. (2021). Analisis yuridis pengelompokan wilayah pada notaris berkaitan norma perhitungan penghasilan neto terkait pejabat umum. Jurnal Cakrawala Hukum, 12(2), 129-138. doi:https://doi.org/10.26905/idjch.v12i2.5811